Identification of a novel recurrent EEF2 gene amplification in familial prostate tumors. Issue 5 (23rd December 2022) - Raspin, Kelsie; Marthick, James R.; Donovan, Shaun; Blizzard, Leigh; Malley, Roslyn C.; Jung, Chol‐hee; Banks, Annette; Redwig, Frank; Skala, Marketa; Dickinson, Joanne L.; FitzGerald, Liesel M.
Abstract: Recurrent tumor copy number variations (CNVs) in prostate cancer (PrCa) have predominantly been discovered in sporadic tumor cohorts. Here, we examined familial prostate tumors for novel CNVs as prior studies suggest these harbor distinct CNVs. Array comparative genomic hybridization of 12 tumors from an Australian PrCa family, PcTas9, highlighted multiple recurrent CNVs, including amplification of EEF2 (19p13.3) in 100% of tumors. The EEF2 CNV was examined in a further 26 familial and seven sporadic tumors from the Australian cohort and in 494 tumors unselected for family history from The Cancer Genome Atlas (TCGA). EEF2 overexpression was observed in seven PcTas9 tumors, in addition to seven other predominantly familial tumors ( n total = 34%). EEF2 amplification was only observed in 1.4% of TCGA tumors, however 7.5% harbored an EEF2 deletion. Analysis of genes co‐expressed with EEF2 revealed significant upregulation of two genes, ZNF74 and ADSL, and downregulation of PLSCR1 in both EEF2 amplified familial tumors and EEF2 deleted TCGA tumors. Furthermore, in TCGA tumors, EEF2 amplification and deletion were significantly associated with a higher Gleason score. In summary, we identified a novel PrCa CNV that was predominantly amplified in familial tumors and deleted in unselected tumors. Our results provide further evidence that familial tumors harbor distinct CNVs, potentially due to an inherited predisposition, but also suggest that regardless of how EEF2 is dysregulated, a similar set of genes involved in key cancer pathways are impacted. Given the current lack of gene‐based biomarkers and clinical targets in PrCa, further investigation of EEF2 is warranted.